2019
DOI: 10.1177/0022219419842914
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Cross-Linguistic Association of Phonological Skills and Reading Comprehension: Evidence From Hong Kong Chinese-English Bilingual Readers

Abstract: This study examined the roles of first-language (L1) Chinese and second-language (L2) English phonological skills in English and Chinese reading comprehension, respectively, and their association with reading comprehension difficulties among Hong Kong Chinese-English bilingual children. We tested 258 second graders on nonverbal intelligence, working memory, phonological skills, word reading, and reading comprehension, in both Chinese and English. Structural equation modeling analyses revealed that Chinese phon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This is likely because NCSs already have relatively strong syllable awareness, so they make relatively minor improvements in their ability to perceive English syllables. Chinese is spoken with syllable timing, and Chinese speakers tend to use syllabic segmentation when reading English words (Deng et al, 2019). Consequently, NCSs may reach the ceiling early on the syllable awareness task (McBride-Chang & Kail, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely because NCSs already have relatively strong syllable awareness, so they make relatively minor improvements in their ability to perceive English syllables. Chinese is spoken with syllable timing, and Chinese speakers tend to use syllabic segmentation when reading English words (Deng et al, 2019). Consequently, NCSs may reach the ceiling early on the syllable awareness task (McBride-Chang & Kail, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we could not completely rule out the possibility that English phonological awareness and alphabetic skills might be correlated with their Cantonese phonological awareness and Jyutping knowledge, and further contribute to the behavioral and neural differences observed between the two groups. Indeed, many aspects of the cross-language transfer effects of phonological awareness and literacy skills remain controversial (including the direction of such transfer effects: L1-to-L2 or L2-to-L1), and the discrepancies could be due to multiple factors (e.g., the phonological and orthographic similarity between two languages; Bialystok et al, 2005 ; Dodd et al, 2008 ; Deng et al, 2019 ). The current finding confirmed the behavioral advantage of alphabetic literacy skills in speech processing in one’s native language and provided further evidence on the underlying neuro-cognitive processes of such effects.…”
Section: Discussionmentioning
confidence: 99%
“…Some Cantonese speakers choose to learn Jyutping primarily for the purpose of inputting Chinese on social media. Although most Cantonese speakers in Hong Kong have some acquaintance with the alphabetic English script, it remains controversial whether learning to read in an alphabetic script of a second language like English would influence their phonological processing in Cantonese in the same way and to the same extent as acquiring an alphabetic script of their native language Cantonese ( Bialystok et al, 2005 ; Dodd et al, 2008 ; Deng et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In studies with NC children, segmental and suprasegmental PA have been consistently identified as strong predictors of word reading skills ( Chung et al, 2013 ; Wei, 2017 ). In their study, Deng et al (2019) examined the relationship between PA and English word reading and reading comprehension abilities in typically developing second-grade students in Hong Kong. They assessed these abilities by measuring English segmental PA (phonemic awareness) through elision and word blending tasks, and suprasegmental PA (stress sensitivity) through tasks that targeted word, intonation, and phrase stress.…”
Section: Introductionmentioning
confidence: 99%